Eco-friendly and safe alternatives for the valorization of shrimp farming waste - Wani, Atif Khurshid; Akhtar, Nahid; Mir, Tahir ul Gani; Rahayu, Farida; Suhara, Cece; Anjli, Anjli; Chopra, Chirag; Singh, Reena; Prakash, Ajit; El Messaoudi, Noureddine; Fernandes, Clara Dourado; Ferreira, Luiz Fernando Romanholo; et al. (Springer Nature, 2023)
The seafood industry generates waste, including shells, bones, intestines, and wastewater. The discards are nutrient-rich, containing varying concentrations of carotenoids, proteins, chitin, and other minerals. Thus, it is imperative to subject seafood waste, including shrimp waste (SW), to secondary processing and valorization for demineralization and deproteination to retrieve industrially essential compounds. Although several chemical processes are available for SW processing, most of them are inherently ecotoxic. Bioconversion of SW is cost-effective, ecofriendly, and safe. Microbial fermentation and the action of exogenous enzymes are among the significant SW bioconversion processes that transform seafood waste into valuable products. SW is a potential raw material for agrochemicals, microbial culture media, adsorbents, therapeutics, nutraceuticals, and bio-nanomaterials. This review comprehensively elucidates the valorization approaches of SW, addressing the drawbacks of chemically mediated methods for SW treatments. It is a broad overview of the applications associated with nutrient-rich SW, besides highlighting the role of major shrimp-producing countries in exploring SW to achieve safe, ecofriendly, and efficient bio-products.
Keywords: Agrochemicals; Applications; Chitin; Chitosan; Nanomaterials; Seafood waste